Corporate Governance and Corporate Social Responsibility Disclosure: The Case of Romanian Companies - Bogdan Aurelian MIHAIL (Communications of International Proceedings, 2021)
This study examines the Corporate Social Responsibility (CSR) disclosure activity as part of good corporate governance practices for the companies listed on the Bucharest Stock Exchange (BSE) Romania for the period 2019-2020, using a new and novel dataset that provides standardised information on CSR disclosures. The results indicate that Romanian companies listed on the BSE have been reporting their CSR activities at an increasing rate, as the relevant rate increased from 43% of companies in 2019 to 49% in 2020. In addition, the regression results show that, after controlling for the firm size and board size variables, the presence of CSR disclosures in the annual reports is positively associated with higher market value for these companies, as measured by Tobin’s Q. The findings imply that CSR disclosure activity can have a positive contribution to improve the corporate governance quality and the market value of the companies listed on the BSE.
Keywords: Corporate Governance; Corporate Social Responsibility; CSR; Environmental; Social; and Governance; ESG; Romania; Firm performance.